Mean Scar Entropy by Late Gadolinium Enhancement Cardiac Magnetic Resonance Is Associated With Ventricular Arrhythmias Events in Hypertrophic Cardiomyopathy - Ye, Yang; Ji, ZhongPing; Zhou, Wenli; Pu, Cailing; Li, Ya; Zhou, Chengqin; Hu, Xiuhua; Chen, Chao; Sun, Yaxun; Huang, Qi; Zhang, Wenjuan; Qian, Yu'e; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Ventricular arrhythmias (VAs) are associated with sudden cardiac death (SCD) in hypertrophic cardiomyopathy (HCM). Previous studies have found late gadolinium enhancement (LGE) on cardiac magnetic resonance (CMR) was independently associated with VA in HCM. Risk stratification of VA remains complex and LGE is present in the majority of HCM patients. This study was to determine whether the scar heterogeneity by LGE derived entropy is associated with VAs in HCM patients. Materials and Methods: Sixty-eight HCM patients with scarring were retrospectively enrolled and divided into VA (31 patients) and in Non-VA (37 patients) groups. Left ventricular ejection fraction (LVEF) and percentage of late gadolinium enhancement (% LGE) were evaluated. Scar heterogeneity was quantified by entropy within the scar and left ventricular (LV) myocardium. Results: Multivariate analysis showed that higher scar (Hazard ratio [HR] 2.682;95% confidence interval [CI]:1.022 to 7.037; p=0.039) was independently associated with VA, after adjustment for LVEF, %LGE, the LV maximal wall thickness (MWT) and the left atrium (LA) diameter. Conclusion: Scar entropy and %LGE are both independent risk indicators of VA. High scar entropy may indicate an arrhythmogenic scar, identification of which may have value for clinical status assessment of VAs in HCM patients.